Usage of E-Tailing Services Among Student Population in Brcko District I Bosnia And Herzegovina (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2020)
The digital revolution, as a change from analogue to digital, has brought about many changes in all spheres of people's lives, including retail. Changes in the way of business are evident in all fields, and, among other things, there is an inevitable transformation of retail. Retail, as a middleman between manufacturer and customer, is experiencing increasing transformation with the development of modern digital technologies. Traditionally, retail was considered to be a physically present object, in which customers must be physically present in order to make a purchase. Today, retailers are increasingly adapting to the needs of the modern customer, and are developing business models that do not require the customer to be present at the retailer to make the purchase. In order to understand the importance of e-tailing for users, a survey was conducted on the use of e-tailing services in the student population of the Brcko District of Bosnia and Herzegovina. The aim of the paper is to determine the extent of use and what are the views on e-tailing by the mentioned population, and the methods used in the work are analysis, synthesis, generalization and statistical methods.